Monitoring bubble size distribution using pressure fluctuations. - Foo, Jing Quan. (2010)
Bubble size and distribution are key monitoring parameters for the heat and mass transfer performance in gas-liquid bubble columns and gas-liquid-sold fluidized bed processes. Many of the techniques currently in use are expensive, time consuming and intrude into the systems. Physical intrusion disrupts the original flow of the bubbles and affects the results obtained.